Interconexión de sistemas eléctricos considerando tecnología HVDC y alternativas de generación (2017)
This thesis proposes a methodology of integrated generation-transmission planning of power systems (G&TEP), that considers the penetration of renewable generation sources and simultaneously the interconnection of independent AC systems by means of HVDC grids. The methodology makes use of differential evolution optimization algorithms to search the optimal solution of the configuration of the HVDC grid and the optimal balance between new generation sources. The methodology is tested on a proposed test system that interconnects IEEE-RTS system and the IEEE 39 bus system and two large generation sources, one a wind farm and the other one large hydroelectric source.